Dynamical alterations of brain function and gut microbiome in weight loss - Zhou, Jing; Wu, Xiaoling; Xiang, Tianyuan; Liu, Fei; Gao, Hui; Tong, Li; Yan, Bin; Li, Zhonglin; Zhang, Chi; Wang, Linyuan; Ou, Lei; Li, Zhongxia; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: Intermittent energy restriction (IER) is an effective weight loss strategy. However, little is known about the dynamic effects of IER on the brain-gut-microbiome axis. Methods: In this study, a total of 25 obese individuals successfully lost weight after a 2-month IER intervention. FMRI was used to determine the activity of brain regions. Metagenomic sequencing was performed to identify differentially abundant gut microbes and pathways in from fecal samples. Results: Our results showed that IER longitudinally reduced the activity of obese-related brain regions at different timepoints, including the inferior frontal orbital gyrus in the cognitive control circuit, the putamen in the emotion and learning circuit, and the anterior cingulate cortex in the sensory circuit. IER longitudinally reduced E. coli abundance across multiple timepoints while elevating the abundance of obesity-related Faecalibacterium prausnitzii, Parabacteroides distasonis, and Bacterokles uniformis. Correlation analysis revealed longitudinally correlations between gut bacteria abundance alterations and brain activity changes. Conclusions: There was dynamical alteration of BGM axis (the commnication of E. coli with specific brain regions) during the weight loss under the IER.